Ceria nanoparticles for the treatment of Parkinson-like diseases induced by chronic manganese intoxication1. Issue 26 (22nd March 2015) - Pinna, Alessandra; Malfatti, Luca; Galleri, Grazia; Manetti, Roberto; Cossu, Sara; Rocchitta, Gaia; Migheli, Rossana; Serra, Pier Andrea; Innocenzi, Plinio
<x xml:space="preserve">Abstract</x> Ceria nanoparticles with controlled size have been studied as antioxidant agents for the in vitro protection of catecholaminergic cells (PC12) exposed to manganese, which is responsible for an occupational form of Parkinson-like disease.